Biodegradation of Pyrene by Candida sp. S1 under High Salinity Conditions - Tony, Hadibarata; Khudhair, Ameer Badr; Kristanti, Risky Ayu; Kamyab, Hesam (Springer, 2017)
Polycyclic aromatic hydrocarbon is a toxic recalcitrant environmental pollutant and its removal from the environment is very essential. In this study, a novel S1 strain isolated from the tropical rain forest was identified as Candida species based on 18S rRNA. The pyrene biodegradation was performed by Candida sp. S1. Pyrene was 35% degraded in 15 days. The percentage of pyrene biodegradation increased up to 75% with 24 g L-1 of sodium chloride and decreased along with increasing salinity. Under the acidic condition, the biodegradation was increased up to 60% at pH 5. It was also found that the increasing glucose concentration of more than 10 g L-1 had no significant effect on pyrene biodegradation, while agitation proved to have greater influence. There was a positive relationship between biomass growth and biodegradation rate of pyrene. One pyrene metabolite was identified from the extract solution and analyzed by a thinlayer chromatography, UV–visible absorption and gas chromatography–mass spectrometry. The metabolite found in the pyrene degradation was benzoic acid.